2017
DOI: 10.21873/invivo.11062
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Netrin-1 in Osteoblast Differentiation

Abstract: Bone tissue is constantly being remodeled to maintain its homeostasis by osteoblasts and the resorption by osteoclasts (1). The function of bone tissue is regulated by several factors which other organs produce to communicate with bones. Indeed, the vessels and nerves inside bone are essential for bone development and remodeling (2, 3). Previous studies have demonstrated that neural and vascular regulation factors, such as semaphorins and netrins, orchestrate bone metabolism. We have demonstrated that semaphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…2) Fb tissue showed higher levels of some genes related to proliferation, selfrenewal or stem cell niche, such as Ptgfr, which acts as a strong mitogenic and survival agent on osteoblasts [12], but Pb tissue expressed high levels of genes associated with anti-proliferative properties, such as AATK and SGOL1, which are both apoptosisrelated proteins [13]. 3) Pb tissue exhibited higher level of osteoblast differentiation by up-regulating genes expressions of Msx2, Twist2, two key transcriptional factor for osteoblast differentiation [14], as well as Ntn1, which plays vital role in osteoblast and osteoclast differentiation [15]. However, Fb tissues expressed higher levels of Ostn and Nell1.…”
Section: Resultsmentioning
confidence: 99%
“…2) Fb tissue showed higher levels of some genes related to proliferation, selfrenewal or stem cell niche, such as Ptgfr, which acts as a strong mitogenic and survival agent on osteoblasts [12], but Pb tissue expressed high levels of genes associated with anti-proliferative properties, such as AATK and SGOL1, which are both apoptosisrelated proteins [13]. 3) Pb tissue exhibited higher level of osteoblast differentiation by up-regulating genes expressions of Msx2, Twist2, two key transcriptional factor for osteoblast differentiation [14], as well as Ntn1, which plays vital role in osteoblast and osteoclast differentiation [15]. However, Fb tissues expressed higher levels of Ostn and Nell1.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to CFU-F clones with high osteoblastic potential, a number of genes were upregulated in CFU-F clones with low osteogenic potential. These include (i) NOTCH2 (twofold upregulated; p = 5.57E−04, FDR = 0.047), which plays a predominant role in suppressing osteoblastogenesis [81]; (ii) COL12A1 (3.49-fold upregulated; p = 1.33E−06, FDR = 1.94E−03), a collagen-encoding gene that forms complexes mediating osteoblast interactions during osteogenesis [82]; (iii) UNC5B (4.51-fold upregulated; p = 4.00E−05, FDR = 1.57E−02), which encodes a netrin receptor involved in negative regulation of osteoblast differentiation by netrin 1 [83, 84]; (iv) TNFRSF19 (4.38-fold upregulated; p = 6.75E−04; FDR = 4.92E−02), which encodes a factor that regulates human MSC differentiation into osteoblasts or adipocytes [85]; and (v) EGLN1 , (2.49-fold upregulated; p = 4.02E−05; FDR = 0.016) which encodes PHD2 (propyl hydroxylase domain 2 protein), a cellular oxygen sensor involved in HIF-α proteosomal degradation in normoxic conditions and inhibiting osteogenic differentiation of MSCs and their upregulation of proangiogenic factors [8688]. Additionally, in those CFU-F with poor vascular supportive capacity, there was an upregulation of TNFSF15 (VEGI), a potent inhibitor of endothelial proliferation and angiogenesis [89].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that Ntn1 inhibits osteoblast differentiation and the combination of two netrin receptors is essential for regulating osteoblast differentiation by Ntn1 (30). Further investigations will be required to clarify the role of netrins in bone metabolism.…”
Section: The Relationship Between Other Netrins and Bone Metabolismmentioning
confidence: 99%